Financial reforms and determinants of FDI: Evidence from landlocked countries in Sub-Saharan Africa - Husam Rjoub; Mehmet Aga; Ahmad Abu Alrub; Murad Bein (Economies, 2017)
The recognition of Foreign Direct Investment (FDI) as a source of funding to foster economic development in both developed and developing countries has been in ascendancy. The prime purpose of this study is to empirically investigate the determinants of FDI for the 'landlocked countries' in Sub-Saharan Africa over the period 1995-2013. By employing panel data analysis, the result of the study revealed that domestic investment, trade (openness), human capital, political constraint, natural resource endowment and the market size (with the GDP growth as proxy) as having positive impact on determining FDI flow into the sample countries with only the countries' tax policies seen otherwise. Our study not only contributes to existing literature on FDI determinants by investigating landlocked countries of Sub-Saharan Africa (SSA) for the first time but also includes natural resources that the landlocked countries are endowed with, tax policies and political constraints in such countries for the stipulated period.
Keywords: F21; C23; 330; FDI; panel GLS; landlocked countries